Effect of mutations across reverse transcriptase region on HBV replication and progression of liver diseases in Chinese patients. Issue 7 (3rd June 2022) - Lai, Xiaoqin; Chen, Wenfa; Wu, Yuzhu; Gao, Yali; Zhang, Yalan; Xu, Xuwei; Fu, Ya; Wang, Xinwen; Yang, Yanbing; Zhang, Yin
Abstract: It was known that mutations in the RT region were mainly related to nucleot(s)ide analogs resistance. Increasing studies indicated that RT mutations were related to advanced liver diseases (ALD) and had effects on HBV replication, but the distribution characteristics of mutations across RT region in the development of liver diseases and the effect of RT mutations on HBV replication were not fully clarified. HBV RT region was direct‐sequenced in 1473 chronic HBV‐infected patients. Mutation frequencies were analyzed to identify the specific mutations differing between groups classified by genotypes, loads of HBV DNA, or progression of liver diseases. In the range of rt145‐rt290, rt145, rt221, rt222, rt267, and rt271 were the genotype‐polymorphic sites, while rt238 was the genotype‐specific sites. Mutations at rt163, rt173, rt180, rt181, rt184, rt191, rt199, and rt214 were more frequent among patients with C‐genotype HBV, while those at rt220, rt225, rt226, rt269, and rt274 were more frequent among patients with B‐genotype HBV. RtM204V/I could reduce the HBV DNA loads while rtQ/L267H/R could increase the HBV DNA loads. RtV214A/E/I (OR 3.94, 95% CI 1.09 to 14.26) was an independent risk factor for advanced liver diseases. In summary, the hotspots of mutations were different between B and C genotypes. Besides the effect on the S region, RT mutations had effects on HBV replication by other unknown ways. RtV214A/E/I was found to be an independent risk factor for ALD, suggesting that mutations at rt214 site could be used as a potential virological marker for the liver disease progression. Abstract : RtM204V/I, causing sW196L within S region, could reduce the HBV DNA loads, while rtQ/L267H/R, without effect on S region, could increase the HBV DNA loads. RtV214A/E/I was found to be an independent risk factor for ALD, being a potential virological marker for the liver disease progression.